Analisis Pengaruh Pengeluaran Konsumsi Pedagang Canang di Pasar Tradisional Kecamatan Denpasar Barat - Dianawati, Weni; Mustika, Made Dwi Setyadhi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
Canang is media or means for Hindu religious ceremonies in Bali, therefore canang’s seller could be one of livelihood as it can become a commercial enterprise, given the high demand for such goods, but not everyone can make it yourself so you should buy. Informal sector is desirable because each family had to find a way out to make ends meet and one of them is consumption. Spending on household consumption has many factors and these conditions can be properly identified in order to influence increased prosperity. This study aimed to analyze the consumption expenditure canang merchants in traditional markets Denpasar District West simultaneously and partially. The sample used in this study were 81 peoples. The analysis technique used in this research is multiple linear regression analysis. Data from this research is using secondary data such as questionnaires or direct interviews with respondents canang merchants. The processed data is simultaneously variable level of education, husband's income, age, number of dependents and the amount of production significantly influence consumption expenditure canang merchants. Partial variable number of dependents and the amount of production and significant positive effect on consumption expenditure canang merchants, while variable levels of education, income and age husband partially no significant effect on consumption expenditures canang merchants.
Keywords: consumption; canang merchants